<< Chapter < Page Chapter >> Page >

We will use the example x 2 + 4 x + 1 = 0 to illustrate each step.

  1. Given a quadratic equation that cannot be factored, and with a = 1 , first add or subtract the constant term to the right sign of the equal sign.

    x 2 + 4 x = −1
  2. Multiply the b term by 1 2 and square it.

    1 2 ( 4 ) = 2 2 2 = 4
  3. Add ( 1 2 b ) 2 to both sides of the equal sign and simplify the right side. We have

    x 2 + 4 x + 4 = 1 + 4 x 2 + 4 x + 4 = 3
  4. The left side of the equation can now be factored as a perfect square.

    x 2 + 4 x + 4 = 3 ( x + 2 ) 2 = 3
  5. Use the square root property and solve.

    ( x + 2 ) 2 = ± 3 x + 2 = ± 3 x = −2 ± 3
  6. The solutions are −2 + 3 , and −2 3 .

Solving a quadratic by completing the square

Solve the quadratic equation by completing the square: x 2 3 x 5 = 0.

First, move the constant term to the right side of the equal sign.

x 2 3 x = 5

Then, take 1 2 of the b term and square it.

1 2 ( −3 ) = 3 2 ( 3 2 ) 2 = 9 4

Add the result to both sides of the equal sign.

x 2 3 x + ( 3 2 ) 2 = 5 + ( 3 2 ) 2 x 2 3 x + 9 4 = 5 + 9 4

Factor the left side as a perfect square and simplify the right side.

( x 3 2 ) 2 = 29 4

Use the square root property and solve.

( x 3 2 ) 2 = ± 29 4 ( x 3 2 ) = ± 29 2 x = 3 2 ± 29 2

The solutions are 3 2 + 29 2 , and 3 2 29 2 .

Got questions? Get instant answers now!
Got questions? Get instant answers now!

Solve by completing the square: x 2 6 x = 13.

x = 3 ± 22

Got questions? Get instant answers now!

Using the quadratic formula

The fourth method of solving a quadratic equation    is by using the quadratic formula    , a formula that will solve all quadratic equations. Although the quadratic formula works on any quadratic equation in standard form, it is easy to make errors in substituting the values into the formula. Pay close attention when substituting, and use parentheses when inserting a negative number.

We can derive the quadratic formula by completing the square    . We will assume that the leading coefficient is positive; if it is negative, we can multiply the equation by −1 and obtain a positive a . Given a x 2 + b x + c = 0 , a 0 , we will complete the square as follows:

  1. First, move the constant term to the right side of the equal sign:

    a x 2 + b x = c
  2. As we want the leading coefficient to equal 1, divide through by a :

    x 2 + b a x = c a
  3. Then, find 1 2 of the middle term, and add ( 1 2 b a ) 2 = b 2 4 a 2 to both sides of the equal sign:

    x 2 + b a x + b 2 4 a 2 = b 2 4 a 2 c a
  4. Next, write the left side as a perfect square. Find the common denominator of the right side and write it as a single fraction:

    ( x + b 2 a ) 2 = b 2 4 a c 4 a 2
  5. Now, use the square root property, which gives

    x + b 2 a = ± b 2 4 a c 4 a 2 x + b 2 a = ± b 2 4 a c 2 a
  6. Finally, add b 2 a to both sides of the equation and combine the terms on the right side. Thus,

    x = b ± b 2 4 a c 2 a

The quadratic formula

Written in standard form, a x 2 + b x + c = 0 , any quadratic equation can be solved using the quadratic formula    :

x = b ± b 2 4 a c 2 a

where a , b , and c are real numbers and a 0.

Given a quadratic equation, solve it using the quadratic formula

  1. Make sure the equation is in standard form: a x 2 + b x + c = 0.
  2. Make note of the values of the coefficients and constant term, a , b , and c .
  3. Carefully substitute the values noted in step 2 into the equation. To avoid needless errors, use parentheses around each number input into the formula.
  4. Calculate and solve.

Solve the quadratic equation using the quadratic formula

Solve the quadratic equation: x 2 + 5 x + 1 = 0.

Identify the coefficients: a = 1 , b = 5 , c = 1. Then use the quadratic formula.

x = ( 5 ) ± ( 5 ) 2 4 ( 1 ) ( 1 ) 2 ( 1 ) = 5 ± 25 4 2 = 5 ± 21 2
Got questions? Get instant answers now!
Got questions? Get instant answers now!

Questions & Answers

More example of algebra and trigo
Stephen Reply
What is Indices
Yashim Reply
If one side only of a triangle is given is it possible to solve for the unkown two sides?
Felix Reply
please I need help in maths
Dayo Reply
Okey tell me, what's your problem is?
Navin
the least possible degree ?
Dejen Reply
(1+cosA)(1-cosA)=sin^2A
BINCY Reply
good
Neha
why I'm sending you solved question
Mirza
Teach me abt the echelon method
Khamis
exact value of cos(π/3-π/4)
Ankit Reply
What is differentiation?
Intakhab Reply
modul questions trigonometry
Thamarai Reply
(1+cosA)(1-cosA)=sin^2A
BINCY
differentiate f(t)=1/4t to the power 4 +8
Jessica Reply
I need trigonometry,polynomial
duru Reply
ok
Augustine
Why is 7 on top
Bertha Reply
simplify cot x / csc x
Catherine Reply
👉🌹Solve🌻 Given that: cotx/cosx =cosx/sinx/cosx =1/sinx =cosecx Ans.
Vijay
what is the period of cos?
SIYAMTHEMBA Reply
your question might not seem clear as you asked. ask well to get perfect answers put your question on a table I'm willing to help you Mr Siyamthemba
Patrick
simplify: cot x/csc x
Catherine
sorry i didnt realize you were actually asking someone else to put their question on here. i thought this was where i was supposed to.
Catherine
some to dereve formula for bulky density
kurash
Solve Given that: cotx/cosx =cosx/sinx/cosx =1/sinx =cosecx Ans.
Vijay
if tan alpha + beta is equal to sin x + Y then prove that X square + Y square - 2 I got hyperbole 2 Beta + 1 is equal to zero
Rahul Reply
questions
Thamarai
ok
AjA
Practice Key Terms 7

Get the best Algebra and trigonometry course in your pocket!





Source:  OpenStax, Algebra and trigonometry. OpenStax CNX. Nov 14, 2016 Download for free at https://legacy.cnx.org/content/col11758/1.6
Google Play and the Google Play logo are trademarks of Google Inc.

Notification Switch

Would you like to follow the 'Algebra and trigonometry' conversation and receive update notifications?

Ask